Data Centre for French Coastal Operational Oceanography - FICHAUT, M.; BONNAT, A.; CARVAL, T.; LECORNU, F.; LE ROUX, J. F.; MOUSSAT, E.; NONNOTTE, L.; TAROT, S. (Mediterranean Marine Science, 2011)
no abstract